Monoethanolamine (MEA) wastewater treatment using Photo-Fenton oxidation - Maszelan, C.N.H.C. (Trans Tech Publications Ltd, 2014)
Monoalkanolamine (MEA) is useful for scrubbing acidic gases such as carbon dioxide (CO2) in flue gas from oil and gas industries. However, small portion of MEA is carried out during the process and being discharged into the wastewater. The organic properties of MEA make it resilience to the conventional wastewater treatment. Photo-Fenton, a potential way of treating the MEA, is a method of producing hydroxyl radical from reaction of ferrous ion, Fe2+ and hydrogen peroxide, H2O2 with UV light. The hydroxyl radicals will then attack MEA and formed the degradation product. The scope of study is to treat synthetic MEA wastewater with the presence of UV light. Different concentration of ferrous ion and hydrogen peroxide is being tested. The removal efficiency is observed through the Total Organic Carbon (TOC) value of the. It is found that the percentage of TOC removal is higher with presence of UV light compared to without UV light. It is also found that for this project, the optimum concentration of ferrous ion is at 0.014M whereby for hydrogen peroxide, the optimum concentration is at 1.6M with both giving highest TOC removal at 99. Â© 2014 Trans Tech Publications, Switzerland.